2013, Nr. 14, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting and auditing challenges Inese Vigante, Ruta Sneidere, Social accounting and its contribution to society, 7 Rasa Kanapickienė, Internal control instruments in the accounting policy of public sector entities, 17 Darius Vaicekauskas, Types of audit quality research: their advantages and disadvantages, 30 Evelina Stankevič, Performance audit analysis done by the national audit office of Lithuania, 41 Gintarė Giriūnienė, Raminta Benetytė, Evaluation of tax audit strategies, 52 Analysis and forecasting of enterprise‘ activity Lukas Giriūnas, Jonas Mackevičius, Romualdas Valkauskas, Clusterization of reasons for bankruptcy of enterprises, 60 Lukas Giriūnas, Aivaras Kazlauskas, Research of companies bankruptcy and its procedure, 72 Judita Urbonaitė, Milda Kvekšienė, Mathematical methods for forecasting the company’s financial results, 83 Research of tax systems Monika Melnykaitė, Agnė Ramanauskaitė, Assessment of bringing in the progressive income taxation in Lithuania, 96 Lina Šalnytė, Giedrė Balkytė, Comparative analysis of Lithuanian and Polish taxation system, 110 Analysis of study process Birutė Jukonienė, Ona Gudaitienė, Melanija Sinevičienė, The final thesis – learning outcome of professional bachelor., 121